LA HISTORIA DE PANTEA EN CUATRO ROMANCES DE JUAN DE LA CUEVA - Gallé Cejudo, Rafael J. (Myrtia, 2002)
Panthea’s tale in four ballads of Juan de la Cueva. In this paper the author analyzes the celebrate Panthea and Abradates’ tale and the literary treatment in the passing from its original literary context –Xenophon’s Cyropaedia - into the new furnished by the paraphrase of Juan de la Cueva in four ballads of his first Coro febeo.